ASYMPTOMATIC BACTERIURIA IN WOMEN PRESENTING TO ANTENATAL CLINIC AT A TERTIARY CARE HOSPITAL IN KARACHI, PAKISTAN: Asymptomatic Bacteriuria in Women - Shuja, Samia; Pario, Saba; Muneeb, Aeman (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency, risk factors, and common causative agents of asymptomatic bacteriuria inpregnant women attending antenatal clinic at JPMC Karachi.Study Design: Cross sectional study.Place and Duration of Study: Jinnah Postgraduate Medical Center Karachi, from Jul 2014 to Sep 2015.Material and Methods: One hundred seventy seven women participated according to pre-determined inclusioncriteria. All of them underwent urine examination on midstream urine and urine was cultured in case of apositive test (>10 leukocytes per microliter of urine).Results: Incidence of asymptomatic bacteriuria was 12.4% of the 177 women. Low socioeconomic status wasfound to be the only statistically significant risk factor associated. The most common causative agent was E. coli.Conclusion: Pregnant women belonging to lower socioeconomic status are more likely to have asymptomaticbacteriuria. The recommendations stemming out of the study include complete examination of urine of allpregnant women to be carried out at first antenatal visit and culture of urine to follow if indicated.